PERLINDUNGAN KEPENTINGAN PELAKU USAHA DI INDONESIA DALAM PERJANJIAN REASURANSI DENGAN REASURADUR LUAR NEGERI - Gunawan, Anton; Ari Yuliartini Griadhi, Ni Made (Kertha Semaya : Journal Ilmu Hukum; Vol. 02, No. 05, Juli 2014)
Interest of Indonesian business people in reinsurance treaties with foreignreinsurers must get a protection. In writting this journal to know relationships of theparties and to know protection of the interests. In writing this journal normativeresearch methods to the analysis of legal materials are presented in a systematic.relationships and responsibilities of the parties to the reinsurance agreement is not atakeover or substitution by one person upon another person. Protection of the interestsof the Indonesian business people in reinsurance treaties with foreign reinsurersbasically on security and ease of placement of reinsurance claims bill.
Keywords: Reinsurance agreements, protection of interests